Comparison of the Electrochemical Behaviour and Self-sealing of Zirconium Conversion Coatings Applied on Aluminium Alloys of series 1xxx to 7xxx. Issue 11 (31st July 2020) - Šekularac, Gavrilo; Kovač, Janez; Milošev, Ingrid
Abstract : Zirconium conversion coatings prepared in a 200 ppm H2 ZrF6 bath for optimal conversion times, were applied on aluminium alloys starting from AA1 xxx up to AA7 xxx series. The electrochemical behaviour and self-sealing abilities of the coatings were studied by electrochemical impedance spectroscopy during their immersion in 0.5 M NaCl for five days. Microstructural and surface characterization were carried out using scanning electron microscopy with energy dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectrometry techniques. All zirconium conversion coatings had a bi-layer structure, with average thickness in the range of 30–60 nm, except for the coating applied on alloy AA2024 which exhibited a single-layer structure with a thickness of 12 nm. The coatings provided excellent corrosion protection and self-sealing behaviour when applied on AA3005, AAA356.0, and very good corrosion protection for AA380.0, AA5754 and AA1050A. On the other hand, these coatings did not provide adequate corrosion protection for AA2024 and AA7075. The results were discussed in terms of the role of intermetallic particles on the properties of the conversion coating.